2020
DOI: 10.1155/2020/9210748
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of PPARγ Targets in Human Extravillous and Villous Cytotrophoblasts

Abstract: Trophoblasts, as the cells that make up the main part of the placenta, undergo cell differentiation processes such as invasion, migration, and fusion. Abnormalities in these processes can lead to a series of gestational diseases whose underlying mechanisms are still unclear. One protein that has proven to be essential in placentation is the peroxisome proliferator-activated receptor γ (PPARγ), which is expressed in the nuclei of extravillous cytotrophoblasts (EVCTs) in the first trimester and villous cytotroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…In our project, we explored the molecular mechanisms behind the regulation of the PGE2 receptor EP4 in trophoblasts in first trimester placentas. Liu et al suggested that PGE2 modulates biochemical and morphological placental trophoblast differentiation during implantation and placentation [17]. Previous research demonstrated that placental hypoxia activated cAMP production, proliferation, and invasion by mediating cAMP-PKA-pCREB signaling in trophoblast cells, predominantly through EP1 and EP4 [18,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our project, we explored the molecular mechanisms behind the regulation of the PGE2 receptor EP4 in trophoblasts in first trimester placentas. Liu et al suggested that PGE2 modulates biochemical and morphological placental trophoblast differentiation during implantation and placentation [17]. Previous research demonstrated that placental hypoxia activated cAMP production, proliferation, and invasion by mediating cAMP-PKA-pCREB signaling in trophoblast cells, predominantly through EP1 and EP4 [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Supernatants were collected from 24-well plates of HTR-8/SVneo, JEG-3, and BeWo cells that had been incubated in defined medium for 24 and 36 h, respectively, and refluxed at 10,000× g for 10 min for filtration of cell sections. β-hCG and progesterone were gauged using the recommended guidelines with an ADVIA Centaur XP auto analyzer (Siemens Medical Solution Diagnostics, Erlangen, Germany), described in previous studies [17].…”
Section: β-Hcg and Progesterone Measurementmentioning
confidence: 99%
“…Different effects were analyzed to characterize their variability including tissue types and gestational days. Data processing further used the methods detailed in Liu et al (2020) . In brief, the threshold to identify the up- and downregulated genes per statistical comparison was set to a fold change of 1.5, and the Gene Ontology (GO) terms (or KEGG pathways) associated with the differential expressions (all DEGs, as well as up- or downregulated DEGs) were recovered using ClueGO.…”
Section: Methodsmentioning
confidence: 99%